PENYELIDIKAN GEOLOGI TEKNIK UNTUK PEMBANGUNAN TANGGUL KALI LOROK PACITAN JAWA TIMUR - Setiono Setiono; Dwiyanto Joko Suprapto; Wahju Krisna Hidajat (Geological Engineering E-Journal, 2014)
Lorok river, Pacitan, East Java is one of the river is located in the south eastern part Pacitan. In this area often flooded due to overflow of river water discharge during the rainy season and at high tide the sea water so that it can be detrimental to the public around the area of research which is along the river flow Lorok. Therefore, the government will undertake the construction of a dike to overcome these problems.In the present study, namely on engineering geology investigation for the construction of levees on the river wall, which aims to determine the condition of the surface geology and subsurface engineering research sites, determine the feasibility of levee, giving advice and know the location, quantity and quality of borrow. So as to provide development planning parameters embankment at the study site.To carry out the construction of the embankment should be known geological conditions of the surface and subsurface techniques. The method used in this study is the investigation of the surface engineering geological and engineering geological mapping subsurface geothecnical investigation with core drilling methods, sondir test and test pit. Mapping of engineering geology carried out in the vicinity of the study. Core drilling carried out by 10 points the BH - 1, BH - 2, BH - 3, BH - 4, BH - 5, BH - 6, BH - 7, BH - 8, BH - 9, BH - 10 with the depth of each point 10 meters. Sondir test conducted by 10 points the SD - 1, SD - 2, SD - 3, SD - 4, SD - 5, SD - 6, SD - 7, SD - 8, SD - 9, SD - 10 with varying depths . In this research, the search pile material in a way to make a well test ( test pit ) by 2 points the TP - 1 and TP - 2. In this investigation will produce approximately engineering geology maps and cross sections of the river flow subsurface engineering geology around the flow of the river.Based on the results of the analysis of the data that had been collected earlier, the recommended embankment foundation planning on hard ground or on rocks. Engineering geology cross-section can show the bedrock or rock beneath the surface as well as the physical and mechanical properties of soil or rock that is on site research.